Response of sulphur fertilization and weed management to performance of faba bean (Vicia faba L.) (Research in Agriculture Livestock and Fisheries, 2023)
The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh from November 2021 to April 2022 to assess the effect of sulphur fertilization and weed management on yield performance of faba bean. The experiment consisted of three levels of sulphur viz. 0, 20 and 40 kg S ha-1 and four levels of weed management practices viz. control (weedy check), weed-free up to 30 days after sowing (DAS), weed-free up to 60 DAS, weed-free throughout the growth period. The experiment was laid out in a randomized complete block design with three replications.  The highest number of branches plant-1 (11.63), pods plant-1 (70.68), seeds pod-1 (5.50), 1000-seed weight (267.9 g), seed yield (2.72 t ha-1), and stover yield (2.93 t ha-1) were recorded with 40 kg ha-1.  In the case of weed management, the highest number of branches plant-1 (10.16), pods plant-1 (66.03), seeds pod-1 (6.0), 1000-seed weight (266.7 g), seed yield (2.43 t ha-1), stover yield (2.85 t ha-1) and harvest index (45.80%) was found at weed free throughout the growth period. Whereas the lowest values of all parameters were found minimum in weedy check. In interaction, the highest number of branches plant-1 (13.0), pods plant-1 (78.69), seeds pod-1 (7.0), 1000-seed weight (269.5 g), seed yield (2.87 t ha-1), stover yield (2.98 t ha-1) and harvest index (49.37%) were found in 40 kg ha-1 S with weed-free throughout the growth period. Whereas the lowest parameters were found minimum in control. Therefore, application 40 kg ha-1 S along with weed-free conditions throughout the growth period appears as the suitable combination for faba bean cultivation.Res. Agric. Livest. Fish. 10(1): 33-42.